The Perspective of Communication Among Acehnese Women in Determining the Amount of Dowry in TiTeue Subdistrict Pidie Regency, Aceh Province - Munawwarah, Putri; Humaizi, Humaizi; Lubis, Lusiana Andriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the communication process of Acehnese women in determining dowry amounts, the role of their families, and the communication strategies used. Theories applied include interpersonal, family, intercultural communication, and dowry. Using a qualitative method, 6 informants (3 married and 3 in serious relationships) from Pidie Regency were interviewed. The findings show that dowry decisions involve effective communication between women and their families, with parents playing a key role. Discussions within the woman's family are then conveyed to the man's family, leading to a final decision. The man’s qualities are prioritized over his ability to provide a high dowry. Data collection was carried out through interviews and. The communication strategv of Acehnese women and their families in determining the dowry involves discussions within the woman's family, which are then conveyed to the man's family, leading to a final decision regarding the dowry amount and whether to proceed with the marriage. The findings indicate that the criteria for the man are the main consideration in choosing a partner, rather than his ability to provide a high dowry that does not meet the criteria.